Preventive management of oral cancer survivor: A case report - Hala F. BenGhasheer; Roslan Saub (DiscoverSys Inc., 2020)
Objective:The most prevalent malignancy of the oral cavity is SCC that is not often seen in young patients. The aim was to report undertaken preventive measures for a clinical case of a young oral cancer survivor with therapy complications who attended at the preventive/ special needs clinic, University of Malaya. Methods:29 years-old, single female, diagnosed with maxillary gingival squamous cell carcinoma at age of 16, with post -therapy complications. A professional cleaning, fluoride therapy, fissure sealant was applied to tooth #36 & #46, and stainless steel crown was constructed on badly decayed #37. In addition to, detailed dietary advice, tailored oral hygiene instructions, and how to self-examine her mouth periodically for changes. Results:Patient is currently under periodic control, including a followup by oral surgery clinic and preventive clinic (University of Malaya) with special focus on preventive measures to maintain good oral health related to such patients. Conclusion: it is crucial to have a good preventive plan that helps the oral cancer survivor to cope with the consequences of cancer treatment and improve their quality of life. Dentists and oral healthcare professionals who are involved in cancer patient’s treatment play a key role in promoting patient’s oral health and improving their quality of life through multidisciplinary clinical planning.